2021
DOI: 10.3390/nu13020460
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Your Himalayan Expedition: Nutritional Signatures and Body Composition Adaptations of Trekkers and Porters

Abstract: High-altitude exposure leads to many physiological challenges, such as weight loss and dehydration. However, little attention has been posed to the role of nutrition and ethnic differences. Aiming to fulfill this gap, five Italian trekkers and seven Nepalese porters, all males, recorded their diet in diaries during a Himalayan expedition (19 days), and the average daily intake of micro and macro-nutrients were calculated. Bioimpedance analysis was performed five times during the trek; muscle ultrasound was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 50 publications
5
11
0
Order By: Relevance
“…The average energy supply with the diet was 2833 kcal/day, which provided an insufficient supply of energy relative to demand. The results of another study showed that a group of Italians and Nepalese during an expedition to the Himalayas supplied, respectively, 2793 kcal/day and 2775 kcal/day, which was not enough in relation to the demand [28]. The dietary energy supply in our study was similar to the results presented above (Table 2).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The average energy supply with the diet was 2833 kcal/day, which provided an insufficient supply of energy relative to demand. The results of another study showed that a group of Italians and Nepalese during an expedition to the Himalayas supplied, respectively, 2793 kcal/day and 2775 kcal/day, which was not enough in relation to the demand [28]. The dietary energy supply in our study was similar to the results presented above (Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…Many studies have been conducted on changes in body composition caused by staying at high altitude [26,27], or approaches to feeding teams of mountaineers in the high mountains [28][29][30]. There is still a lack of precise guidelines on nutrition in high-mountain conditions, focused on the real needs and referring to the preferences of climbers.…”
Section: Introductionmentioning
confidence: 99%
“…The average daily intake of participants, estimated from food diaries loaded into an ad-hoc web database [ 22 ], included 39 ± 9 g (13 ± 2% of the total energy intake) of PUFAs among other nutrients and 3000 ± 500 g of water. The trekkers suffered the combined stress of physical exercise and hypoxia, as elsewhere reported with a suppression of the hypothalamus-pituitary gonadal axis and altered thyroid metabolic function [ 38 ], a weight loss and a reduction in total body water [ 22 ], while the mood disturbance scores were lower at high altitude [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…First-void urinary samples were immediately frozen at −20 °C and stored until analysis. Daily food, water, MUFA, and PUFA intake were self-recorded by the subjects, on three non-consecutive days during the trek [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is reasonable to assume that the reduction we observed was determined, rather than a disruption in the production processes, by a loss of bodily fluid and sodium triggered by augmented diuresis and natriuresis commonly induced at high altitudes [ 52 ]. Indeed, previous results have shown a loss of bodily fluids in the participants of the “Kanchenjunga Exploration and Physiology” project through a series of bioimpedance analyses during the expedition [ 53 ]. The recovery of volume at Follow-up supports this physiological interpretation.…”
Section: Discussionmentioning
confidence: 99%